2015
DOI: 10.1080/02687038.2014.996520
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia therapy early after stroke: behavioural and neurophysiological changes in the acute and post-acute phases

Abstract: Background: There is reasonable evidence to suggest that speech and language therapy can be effective in the chronic stages of stroke recovery. However, the active ingredients remain unknown and several variables can influence therapy outcome, such as content, type, and amount of therapy. Neurophysiological measures, event-related brain potentials such as the N400 and P300, have shown to be sensitive markers of therapeutic effects. As a supplement to the usual behavioural evaluation methods, neurophysiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 77 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…Third, each therapy investigated had to focus specifically on one, maximally two, linguistic domain(s): semantics, phonology, syntax, orthography, and/or melody/rhythm, to enable the identification of brain changes after training of these specific types of language processing (aim 1). For this reason, studies providing mixed conventional therapy (e.g., Aerts et al, 2015), intention treatment (e.g., Benjamin et al, 2014), action observation treatment (e.g., Gili et al, 2017), interventions on the activity/participation level, imitation therapy (e.g., Santhanam, Duncan, & Small, 2018), script training (e.g., Fridriksson, Hubbard, et al, 2012), or constraint-induced language therapy (e.g., McKinnon et al, 2017) were not considered. We also excluded studies that combined language therapy with noninvasive brain stimulation and/or drug trials, intervention studies in bilingual aphasia, non-peer-reviewed reports, and studies that were not available in English.…”
Section: Review Methods Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Third, each therapy investigated had to focus specifically on one, maximally two, linguistic domain(s): semantics, phonology, syntax, orthography, and/or melody/rhythm, to enable the identification of brain changes after training of these specific types of language processing (aim 1). For this reason, studies providing mixed conventional therapy (e.g., Aerts et al, 2015), intention treatment (e.g., Benjamin et al, 2014), action observation treatment (e.g., Gili et al, 2017), interventions on the activity/participation level, imitation therapy (e.g., Santhanam, Duncan, & Small, 2018), script training (e.g., Fridriksson, Hubbard, et al, 2012), or constraint-induced language therapy (e.g., McKinnon et al, 2017) were not considered. We also excluded studies that combined language therapy with noninvasive brain stimulation and/or drug trials, intervention studies in bilingual aphasia, non-peer-reviewed reports, and studies that were not available in English.…”
Section: Review Methods Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The study found that rehabilitation in the early phases is correlated with increased recruitment of left IFG on tb-fMRI, which lasted over time and improved object naming (Mattioli et al, 2014). A singlecase study reported the beneficial role of early therapeutic intervention by monitoring event-related potentials (ERPs) at electroencephalography (EEG), which have been proven to be useful in monitoring language abilities in aphasia patients (Aerts et al, 2015). Other recent clinical studies showed no deficit improvement after early aphasia treatment (Coleman et al, 2017;Nouwens et al, 2017).…”
Section: Acute Phasementioning
confidence: 99%
“…In a single-case study design, Aerts et al followed the effects of 90 hours of speech therapy (that included elements of auditory training) on a patient with acute, global aphasia using EEG [3]. As the therapy started on day 10 post-stroke and finished on day 105 it was no surprise that many of his language measures improved.…”
Section: Perception Of Languagementioning
confidence: 99%